Differences between the Group Investigation (GI) Learning Model and TGT (Team Games Tournament) Learning Model On Creativity in Civics Learning Class X MAN Panyabungan - Yusmiati, Yusmiati; Daulay, Kausar; Herlina, Herlina (International Journal of Educational Research Excellence (IJERE), 2025)
This research has a problem formulation, namely whether there is a difference between the Group Investigation (GI) Learning Model and the TGT (Teams Games Tournament) Learning Model on Civics Learning Creativity of Class X MAN Panyabungan?. While the goal is to find out the difference between the group investigation (GI) learning model and the TGT (teams games tournament) learning model on Civics learning creativity of class X MAN Panyabungan. The type of research is comparative quantitative, The population in the study were all students of class X MAN Panyabungan consisting of 10 classes totaling 351 students. The sampling technique used was random sampling technique of 70 students, consisting of two classes: class X IIS 2 as many as 35 and class X MIA 6 as many as 35. Data collection used a questionnaire. The data analysis technique used the t-test polled variance formula. Based on the results of the analysis, the calculated t was 1.926 and the t table was 1.67 at an error level of 0.05. so it is known that thitung > ttabel (1.926>1.671) with a sample of 35 + 35– 2 = 68, then the degree of freedom (dk) is 68. It can be concluded that there is a difference between the Group Investigation (GI) learning model and the TGT (Teams Games Tournament) learning model on civics learning creativity in class X MAN Panyabungan.